Anti obese potential of Cucurbita maxima seeds oil: effect on lipid profile and histoarchitecture in high fat diet induced obese rats. Issue 24 (17th December 2018) - Kalaivani, A.; Sathibabu Uddandrao, V. V.; Brahmanaidu, P.; Saravanan, Ganapathy; Nivedha, P. R.; Tamilmani, P.; Swapna, K.; Vadivukkarasi, Sasikumar
Abstract: In this study, we made an attempt to evaluate the potential of Cucurbita maxima seeds oil (CSO) against high-fat diet (HFD)-induced obesity in rats. We investigated the effect of CSO (100 mg/kg body weight) supplementation over 30 days on the changes of HFD-induced obese rats in body weight, biochemical parameters and lipid profile as well as investigated the effects of CSO on the histopathological changes. Oral administration with CSO revealed significant diminution in body weight gain, glucose and insulin levels, which altered the activity of lipid profile and restored the pathological alterations. It demonstrated that CSO had considerably altered these parameters when evaluated with HFD control rats. In conclusion, this study established that CSO prevents the HFD-induced obesity by altering the markers important to lipid metabolism. Abstract :